Tribological behavior of nickel aluminum-silver solid-lubricating alloy coupled with different tribo-pairs lubricated by seawater. (March 2019) - Zhu, Shengyu; Ma, Jiqiang; Tan, Hui; Cheng, Jun; Yu, Yuan; Qiao, Zhuhui; Yang, Jun
Abstract: In this paper, the matching properties of nickel aluminum-silver solid-lubricating alloy coupled with various tribo-pairs in seawater environment were investigated. The results revealed that the Ni3 AlAg alloy mating with Al2 O3 is an appropriate tribo-pair compared with the SiC and 316L steel counterparts. The Ni3 AlAg alloy rubbing against Al2 O3 exhibits the desirable lubricating properties because mild plowing effect contributes to slightly mechanical action and Ag distributed on the worn surface brings the surface shearing stress down. When the Ni3 AlAg alloy is coupled with SiC, the increasing plowing effect and slight material transfer deteriorate the friction behavior. As for the 316L steel counterface, the aggravation of plowing effect and the formation of ferric oxide play adverse roles in tribological behavior. Highlights: Ni3 AlAg alloy coupled with Al2 O3 exhibits low friction coefficient in seawater. The mild furrow and Ag improve tribological behavior of Ni3 AlAg/Al2 O3 tribo-pair. The increasingly plowing and slight material transfer deteriorate SiC counterface. The coarse plowing and ferric oxide exacerbate steel counterface.